A pricing and acquisition strategy for new and remanufactured high-technology products - Liangchuan Zhou; Surendra M. Gupta (Logistics, 2019)
New generations of high-technology products are frequently launched before the previous model is sold out. Customers have an incentive to end the use of their old product and purchase a new one with the latest technological innovations. The unsold old models become less attractive, while the supply of remanufactured products from end-of-use products is uncertain in time, quantity, and quality. Other than adjusting the price, upgrading the returning unsold new products may be a source of remedy. This study provides profit maximization models associated with customer choice demand functions based on manufacturer, retailer, and joint supply chain scenarios. Two acquisition strategies are compared: acquire end-of-use products only and collect both end-of-use products and unsold old-style new products. The results reveal that returning the optimal quantity of overstocked new products brings about a greater benefit in all scenarios. Compared to the remanufacturer, the retailer is the optimal undertaker for collecting used products. In addition to this, slow technological development of the new-generation model causes a decrease in profit for the manufacturer. The optimal quantity of new products to be bought back decreases, because both the manufacturer and the retailer prefer to promote unsold outmoded products rather than upgrade the used products.
Keywords: 650; Acquisition; Generations; High-Technology; Pricing; Remanufacturing